Analysis of Medan City Public Preferences to Become Sharia Insurance Participants - Awaliya Awaliya; Marliyah Marliyah; Tri Inda Fadhila Rahma (SAINTIS Publishing, 2025)
This study aims to analyze the preferences of the Medan City community in choosing sharia insurance by considering various factors, such as the level of religiosity, financial literacy, service quality, and socio-economic aspects. This study uses a qualitative approach with an in-depth interview method with five respondents from various professional and social backgrounds. The results of the study show that the community's understanding of sharia insurance is still diverse. Some people understand the concept of mutual cooperation (ta'awun), but many still have doubts regarding the transparency of fund management and the real benefits provided. The religiosity factor plays an important role in community decisions, but the low level of financial literacy is the main obstacle in understanding the benefits of sharia insurance. In addition, the affordability of premiums, ease of the claim process, and innovation in marketing also influence community preferences. The main challenges in increasing community participation include lack of education and socialization, negative stigma towards insurance, and the assumption that sharia insurance claims are more complicated than conventional insurance. To overcome these challenges, sharia insurance companies need to improve digital-based education, involve religious figures in socialization, and develop products that are more flexible and in accordance with the needs of various segments of society. With the right strategy, sharia insurance can be a more inclusive financial protection solution that is in accordance with sharia principles.